قرآنِ حکیم کی قراءات متواترہ اور استنباط احکام - حافظ تاج افسر; پروفیسر ڈاکٹر سعید الرحمٰن (FIKR-O NAZAR فکر ونظر, 2010)
Variant readings of some of the words of the Qur’an taught by the Prophet (peace be on him) is an interesting phenomenon which has attracted attention of the scholars as well as that of general readers of the Quran. The science of recitations of the Qur’an (’ilm al-Qiraat) is considered to be of vital importance among various Sciences of the Qur’an (’ulam al-Qur’an) as well as Sciences of the Tafsir (’ulum al-Tafsir). The scholars of Tafsir have extensively used those recitations which have been transmitted by multitude of people to multitudes of people in each generation (al-Qiraat al-Mutawatirah) in deduction and extraction of the injunctions (ahkam) pertaining to various aspects of individual and collective spheres of life. This article delves into the classical as well as contemporary works of tafsir and ’ulum al-Qur’an to bring to the fore various issues related to al-qiraat al-mutawatirah. The special focus of this article, however, is to highlight the attempts of the exegetes (al-mufassirin) in fully employing al-qiraat al-mutawatirah in deduction of injunctions (istinbat al-ahkam) as well as in determining the preference or otherwise of the juristic opinions of various schools of thought (madhahib) in Islam۔